The State of Welfare: Crises and Challenges - Platt, Anthony M. (Social justice, 2004)
Part of a special issue on resisting militarism and globalized punishment. The text is provided of a speech given at the opening plenary of the 21st Annual Baccalaureate Social Work Education Conference in Reno, Nevada, on October 29, 2003. The writer argues for the need to change the way in which social work policy and history are taught. He suggests that this can be done by: making social work history into what Raphael Samuel described as an “argument with the past”; developing an interdisciplinary approach; making a comparative framework and a political history of dissent part of the core of social work courses; and being honest and open about the discipline's history.